Structural-acoustic coupling effect of a rectangular cavity comprising a windowpane and five rigid walls and its control (Experimental approach) - Ryoji FUKUDA; Nobuo TANAKA (Nihon Kikai Gakkai ronbunshu, 2015)
This paper deals with a structurally-acoustically coupled rectangular cavity comprising a flexible windowpane and five rigid walls. It is the purpose of this paper to perform active control of a windowpane with a view to enhancing its transmissibility loss. First, using an operational modal analysis the coupling effect emerging on the windowpane under a strongly coupled cavity is investigated. It is then found that there exist two kinds of coupled modes: one is dominated by an in vacuo vibration mode of a panel and the other by an acoustic cavity mode. Among the latter modes an isolated implosive mode is found, which is predominantly governed by an acoustic cavity mode due to a specific support of a windowpane. It is further revealed that the isolated implosive mode may not be suppressed by vibration control, but by acoustic control only. Finally, active structural-acoustic control is performed on the windowpane, demonstrating sufficient control effect over all the coupled modes with synergy effect as a result of employing both vibration and acoustic control.